The Influence of TPACK Mastery and Emotional Intelligence on Teachers’ Technology Awareness - Budiningsif, Iffah; Yasin, Moh. Fahri; Khasanah, Khasanah; Khadijah, Khadijah (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – Technology plays an essential role in the learning process; therefore, technological awareness is a necessary competence for teachers. This study aims to examine the influence of mastery of Technological Pedagogical and Content Knowledge (TPACK) and emotional intelligence on teachers' technological awareness.Method – This study employed a survey method involving teachers from the East Jakarta area who graduated from the Master of Educational Technology program at As-Syafi'iyah Islamic University Jakarta in 2024 (within UIA’s East Jakarta working area). A total of 84 participants were included in the sample. Data were collected using a questionnaire and analyzed through descriptive statistics, correlation analysis, and simple regression. Findings – The results show that teachers' levels of technological awareness, TPACK mastery, and emotional intelligence are within the moderate range, with mean scores between 3.60 and 3.90. There is a positive and moderately strong correlation (R = 0.489) between TPACK mastery and emotional intelligence with technological awareness. Together, TPACK and emotional intelligence explain 23.90% of the variance in technological awareness, indicating that these factors contribute meaningfully to teachers’ awareness of technology use. Among the two variables, emotional intelligence demonstrates a stronger predictive influence on technological awareness compared to TPACK mastery. The regression model Y = 1.587 + 0.215X? + 0.389X? is statistically significant and can be used to predict the level of technological awareness among teachers. Research Implications – Teachers are encouraged to enhance their technological awareness by integrating TPACK more actively in the learning process, supported by emotional resilience such as perseverance and patience when guiding students.